Rethinking stakeholder engagement: A multidimensional framework inspired by meta-synthesis of food, energy, and water research - Paula Williams; J. Leah Jones-Crank; Bassel Daher; Alyssa Thomas; Erin Cortus; Erich Seamon; Andrew Kliskey (Environmental Science & Policy, 2026)

Integrating Health in the Water-Energy-Food Nexus: A Comprehensive Review of Interdependencies, Challenges, and Future Research Opportunities - Rashed Albatayneh; Rabi Mohtar; Zainab Ashkanani; Bassel Daher; Wael K. Al-Delaimy (Current Environmental Health Reports, 2025)
Purpose of Review The Water-Energy-Food (WEF) Nexus has become a crucial framework for understanding resource interdependencies, nevertheless its integration with health remains underexplored. This review paper examines the current literature in the Water Energy Food Health (WEFH) Nexus, emphasizing the complex relationships between resource security and public health outcomes. Through a systematic literature review, the existing research trends, methodological approaches, and regional disparities in WEFH studies are analyzed. Recent Findings While health is an inherent component of resource systems, it is often treated as an externality rather than a central determinant. The review revealed that out of 1175 research articles screened, only 21 discussed WEFH as an integrated nexus. Hence, there is a crucial need for a comprehensive Water, Energy, Food, and Health research. Summary The paper proposes a conceptual WEFH integration that positions health as both an outcome and a driver of sustainable resource management based on epidemiological evidence. By analyzing health metrics implicit to the WEF nexus, the study provides insights for researchers and policymakers seeking to develop holistic strategies for resilience and equity in resource governance.

Inclusive policy development from the ground up: Insights from the household water-energy-food nexus - Maha Al-Zu’bi; Tafadzwanashe Mabhaudhi; Bassel Daher; Youssef Brouziyne (Environmental Science & Policy, 2025)

Coproducing water-energy-food Nexus actionable knowledge: Lessons from a multi-actor collaborative learning school in Uganda, East Africa - Ida N.S. Djenontin; Bassel Daher; Jacob W. Johnson; Kenan Adule; Birhanu K. Hishe; Patience Kekirunga; Vanessa King; Emma Gaalaas Mullaney; Patience Nimushaba; Michael G. Jacobson; Annette Huber-Lee; Ellen J. Kayendeke; et al. (Environmental Science & Policy, 2025)